CHOLECYSTOKININ-LIKE IMMUNOREACTIVE RETINAL GANGLION-CELLS PROJECT TO THE VENTRAL LATERAL GENICULATE-NUCLEUS IN PIGEONS - Britto, LRG; Hamassakibritto, D. E. (Elsevier B.V., 1991)
A subpopulation of retinal ganglion cells projecting to the pigeon ventral lateral geniculate nucleus was shown to contain cholecystokinin-like immunoreactivity. These ganglion cells were mainly distributed in the peripheral retina, and their somata sizes were medium to large (14-23-mu-m). Taken together with previous findings, these results indicate that the retinal input to the ventral geniculate is chemically heterogeneous.
Keywords: CHOLECYSTOKININ; NEUROPEPTIDE; NEUROTRANSMITTER; RETINAL GANGLION CELL; SUBCORTICAL VISUAL PATHWAY; VENTRAL GENICULATE NUCLEUS